The chronology and function of a new circular mammoth-bone structure at Kostenki 11. (April 2020) - Pryor, Alexander J.E.; Beresford-Jones, David G.; Dudin, Alexander E.; Ikonnikova, Ekaterina M.; Hoffecker, John F.; Gamble, Clive
Abstract: Abstract : Circular features made from mammoth bone are known from across Upper Palaeolithic Eastern Europe, and are widely identified as dwellings. The first systematic flotation programme of samples from a recently discovered feature at Kostenki 11 in Russia has yielded assemblages of charcoal, burnt bone and microlithic debitage. New radiocarbon dates provide the first coherent chronology for the site, revealing it to be one of the oldest such features on the Russian Plain. The authors discuss the implications for understanding the function of circular mammoth-bone features during the onset of the Last Glacial Maximum.